The equation of the quadratic function is: [tex]y=\frac{1}{9}x^2+\frac{4}{3}x+3[/tex]
Explanation
The two roots of the quadratic function are given as -9 and -3
So, the associative factors for those two roots will be [tex](x+9)[/tex] and [tex](x+3)[/tex]
Thus, the quadratic function will be: [tex]y=a(x+9)(x+3)........................(1)[/tex]
Now the vertex is at (-6, -1). As the vertex lies on the graph of this quadratic function, so that vertex point will satisfy equation (1).
So, plugging x= -6 and y = -1 into the equation (1)..........
[tex]-1=a(-6+9)(-6+3)\\ \\ -1=a(3)(-3)\\ \\ -1=-9a\\ \\ a= \frac{1}{9}[/tex]
So, the quadratic function will be.....
[tex]y=\frac{1}{9}(x+9)(x+3)\\ \\ y=\frac{1}{9}(x^2+12x+27)\\ \\ y=\frac{1}{9}x^2+\frac{4}{3}x+3[/tex]